2021
DOI: 10.1001/jamanetworkopen.2021.23405
|View full text |Cite
|
Sign up to set email alerts
|

Association of Jail Decarceration and Anticontagion Policies With COVID-19 Case Growth Rates in US Counties

Abstract: IMPORTANCE Mass incarceration is known to foster infectious disease outbreaks, amplification of infectious diseases in surrounding communities, and exacerbation of health disparities in disproportionately policed communities. To date, however, policy interventions intended to achieve epidemic mitigation in US communities have neglected to account for decarceration as a possible means of protecting public health and safety.OBJECTIVE To evaluate the association of jail decarceration and government anticontagion … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 66 publications
1
28
0
Order By: Relevance
“…Regulated release worked best in overcrowded prisons to reduce the risk of infection. Reinhart, E. et al [35] claimed that controlled decarceration reduced the infection rate by eight times in overcrowded prisons, while the use of masks reduced the infection rate by…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Regulated release worked best in overcrowded prisons to reduce the risk of infection. Reinhart, E. et al [35] claimed that controlled decarceration reduced the infection rate by eight times in overcrowded prisons, while the use of masks reduced the infection rate by…”
Section: Resultsmentioning
confidence: 99%
“…Regulated release worked best in overcrowded prisons to reduce the risk of infection. Reinhart, E. et al [ 35 ] claimed that controlled decarceration reduced the infection rate by eight times in overcrowded prisons, while the use of masks reduced the infection rate by 2.5%, while the visit ban reduced the infection rate by 1.2%. Brinkley-Rubinstein, L. et al [ 30 ] concluded that inter-prison transfers reduced the risk of COVID-19 infection.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“… 13 In a recent analysis, Reinhart and Chen ( 2021 , p. 1) found that “anticontagion policies, including jail decarceration to minimize carceral outbreaks and their spillover to surrounding communities, appear to be necessary for epidemic control, public health, and mitigation of racial health disparities.” …”
Section: Endnotesmentioning
confidence: 99%